Indian Sketches : Taken During an Expedition to the Pawnee Tribes in 1833. - Irving, John Treat (Narrative Press, the, 2004)
John Treat Irving, Jr. set off west in the footsteps of his famous uncle, Washington Irving, at the tender age of 20 years. Indian Sketches chronicles his experiences traversing the prairie and living among the Pawnees, Otoes, and other tribes.